Inhibition of lipid synthesis in isolated rat hepatocytes by serum lipoproteins - BARRY COOPER; SIMEON MARGOLIS (Journal of Lipid Research, 1971)
The incorporation of labeled acetate into lipids was studied in rat hepatocytes isolated after treatment of liver with collagenase and hyaluronidase. About 60% of the lipid radioactivity was in free cholesterol and 13% was in triglycerides. Acetate incorporation was markedly inhibited when human serum lipoproteins were present in the incubation medium. Very low, high, and low density lipoproteins, at concentrations of 1.0 mg/ml, inhibited acetate incorporation by 70, 55, and 35%, respectively. Chylomicrons, at similar concentrations, did not inhibit acetate incorporation. The distribution of radioactivity into lipid classes was unchanged by the addition of lipoproteins. Lipoproteins did not produce a nonspecific toxic effect on hepatocytes, since their addition did not alter the rate of leucine incorporation into protein. The addition of the delipidated protein from low density lipoprotein or of lecithin in amounts comparable to those present in inhibitory concentrations of lipoproteins failed to diminish acetate incorporation. Artificial cholesterol–lecithin emulsions containing small amounts of free cholesterol did not inhibit lipid synthesis. Although the mechanism for the inhibition of acetate incorporation by lipoproteins is unclear, such effects may play some physiological role in the control of lipid biosynthesis in the liver.